Integrated semi-transparent spraying-free washing machine panel, panel material and preparation method of panel material

By preparing an integrated semi-transparent, paint-free washing machine panel material, the problems of cumbersome and costly lamination processes have been solved, resulting in improved chemical resistance, toughness, and hardness, and enhanced panel light transmittance and appearance.

CN119505436AInactive Publication Date: 2025-02-25HEFEI COBEL ADVANCED PLASTICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411630367.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing film coating process for washing machine panels is cumbersome and costly, and may result in problems such as bubbling, wrinkling, uneven bending, and peeling. Furthermore, the film coating material is difficult to recycle.

Method used

A one-piece semi-transparent, paint-free washing machine panel material is used. It is formed by mixing a thermoplastic resin composition, antioxidant, weather resistant agent and high-purity aluminum powder, granulating with a twin-screw extruder and injection molding with a mold to form a panel with a semi-transparent effect.

Benefits of technology

It improves the chemical resistance, toughness, and hardness of the panel, reduces production costs, enhances the light transmittance and heat resistance of the panel, and improves processability and appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an integrated semi-transparent spraying-free washing machine panel, a panel material and a preparation method of the panel material. The integrated semi-transparent spraying-free washing machine panel is prepared from the following raw materials in parts by weight: 95-98 parts of a thermoplastic resin composition, 0.1-1 part of high-purity aluminum powder, 0.2-1.0 part of an antioxidant, 0.5-1.0 part of a weather-resistant agent and 0.5-1.0 part of a lubricant. The preparation method of the thermoplastic resin composition comprises the following step: blending the styrene-acrylonitrile copolymer (SAN), the polymethyl methacrylate (PMMA), the core-shell toughening agent and the maleic anhydride grafted compatilizer in a high-speed mixer for 5-20 minutes to obtain the thermoplastic resin composition. By adding the high-chemical-resistance resin SAN and PMMA, the core-shell toughening agent, the maleic anhydride grafting compatilizer and the like, the chemical resistance and toughness of the thermoplastic resin composition can be effectively improved, the possibility of cracking of an integrated washing machine panel product is reduced, and the qualification rate of the product is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of spray-free parts, and in particular to an integrated semi-transparent spray-free washing machine panel and panel material and a preparation method thereof. Background Art

[0002] Conventional washing machine panels are a combination of spray-free parts and control panels, which affects the overall aesthetics of the parts and is very expensive. Spray-free plastics not only improve the appearance and texture of the product, but also help reduce production costs and environmental impacts, making them an ideal environmentally friendly material choice. In order to improve the overall sensory effect of the washing machine control panel and reduce costs, more and more OEMs tend to integrate washing machine panels, that is, the control screen appears in the working state, and consumers perform laundry operations according to their needs. In the non-working state, the control screen is hidden, and the sensory integration is achieved. At present, in order to achieve this effect, the industry mostly uses lamination, but the lamination process is cumbersome and costly, and may also cause problems such as bubbling, wrinkles, uneven bending, and shedding and separation, and the materials after lamination are difficult to recycle and utilize.

[0003] Therefore, from the user's perspective, developing semi-transparent spray-free materials with good appearance, high product grade, good performance and low comprehensive material cost has become an important product development direction. Summary of the invention

[0004] In order to solve the problems mentioned in the above background technology that the laminating process is complicated, costly, and may also cause bubbling, wrinkling, uneven bending, falling off and separation, the present invention provides an integrated semi-transparent spray-free washing machine panel and panel material and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] An integrated semi-transparent spray-free washing machine panel material is made of the following raw materials in parts by weight: 95-98 parts of a thermoplastic resin composition, 0.1-1 parts of high-purity aluminum powder, 0.2-1.0 parts of an antioxidant, 0.5-1.0 parts of a weathering agent, and 0.5-1.0 parts of a lubricant.

[0007] Preferably, the method for preparing the thermoplastic resin composition comprises the following steps:

[0008] Styrene acrylonitrile copolymer (SAN), polymethyl methacrylate (PMMA), core-shell toughening agent and maleic anhydride grafting compatibilizer are blended in a high-speed mixer for 5-20 minutes to obtain a thermoplastic resin composition.

[0009] Preferably, the mass ratio of the styrene acrylonitrile copolymer (SAN), polymethyl methacrylate (PMMA), core-shell toughening agent and maleic anhydride grafted compatibilizer is (30-50): (30-50): (10-25): (2-10);

[0010] The maleic anhydride grafted compatibilizer has a maleic anhydride content of 10%.

[0011] The core-shell toughening agent has a core-shell ratio of (60:40)-(80:20); and the content of GMA is 0-8%.

[0012] By adding highly chemical-resistant resins SAN and PMMA, as well as core-shell toughening agents, maleic anhydride grafted compatibilizers, etc., the chemical resistance and toughness of the thermoplastic resin composition can be effectively improved, the possibility of product cracking can be reduced, and the qualified rate of products can be improved. Among them, the toughening agent with a core-shell structure has good high impact resistance and transparency, and its shell is grafted with GMA with epoxy groups, which has high reaction activity. GMA is a chain extender, which can react the terminal groups of the molecular chain to form a "bridge" to connect the molecular chains, so that the composite material has a higher modulus; the maleic anhydride grafted compatibilizer can significantly improve the tensile strength and impact strength of the composite material.

[0013] Preferably, the preparation method of the core-shell structure toughening agent comprises the following steps:

[0014] Deionized water, emulsifier, reducing agent, chelating agent and polybutadiene latex are placed in a reaction kettle, and nitrogen is introduced. The mixture is stirred at 65°C for 15-30 minutes. After uniform mixing, a mixture of styrene monomer, methyl methacrylate monomer, glycidyl methacrylate and initiator is slowly added into the reaction kettle. After the addition is completed, the temperature is raised to 70°C, and the mixture is aged for 60-120 minutes. A magnesium sulfate solution is added for demulsification and coagulation, and the mixture is washed and dried to obtain a toughening agent with a core-shell structure.

[0015] The initiator is one or more of diisopropylbenzene peroxide, cumene hydroperoxide, and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane;

[0016] The emulsifier is one or more of potassium disproportionate rosin acid, potassium soap of fatty acid, and sodium dodecylbenzene sulfonate;

[0017] The reducing agent is one or more of glucose, ferrous sulfate, and sodium formaldehyde sulfoxylate;

[0018] The chelating agent is one or more of sodium pyrophosphate, tetrasodium ethylenediaminetetraacetic acid, and sodium tripolyphosphate;

[0019] Preferably, the method for preparing the high-purity aluminum powder comprises the following steps:

[0020] The aluminum powder crude product was ball milled for 5-8 hours, and the surface of the aluminum powder after ball milling was treated with a silane coupling agent. The aluminum powder after ball milling was placed in anhydrous ethanol, stirred for 30-60 minutes, filtered, and dried. The washed aluminum powder was placed in anhydrous ethanol solvent, ultrasonically dispersed for 30-60 minutes, and after the end of the ultrasonic, a certain amount of silane coupling agent and a corresponding proportion of deionized water were added, and the mixture was treated at a constant temperature of 50°C for 4-6 hours. After filtering, vacuum drying was performed to obtain surface-modified high-purity aluminum powder.

[0021] The silane coupling agent is one or more of KH540, KH550 and KH570, and the mass ratio of the washed aluminum powder, anhydrous ethanol, silane coupling agent and deionized water is 100:(150-200):(5-10):(10-20).

[0022] Surface modification of aluminum powder can effectively improve the compatibility of aluminum powder with polymer resin, increase the dispersibility of metal particles in the resin, reduce its influence on the mechanical properties of the material, and make the composite material have higher gloss.

[0023] Preferably, the antioxidant is one or more of antioxidant 1076, antioxidant 1010 or antioxidant 168;

[0024] The lubricant is one or more of polyethylene wax, ethylene bis stearic acid amide or calcium stearate.

[0025] Preferably, the weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of (1-1.5):(2.3-3):1.

[0026] 2-(2'-Hydroxy-5'-tert-octylphenyl)benzotriazole (UV-329) as the main ultraviolet absorber can efficiently absorb ultraviolet light of 270-340 nanometers and significantly reduce the destructive effect of ultraviolet rays on materials. The addition of 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol and polyethylene glycol monomethyl ether methacrylate can significantly improve the light stability of the weathering agent and prevent the material from degradation or aging under light. The three ingredients can form a synergistic enhancement effect after being compounded, further improving the ultraviolet protection performance of the weathering agent.

[0027] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0028] S1: Mixing the thermoplastic resin composition, high-purity aluminum powder, antioxidant, weathering agent and lubricant in a high-speed mixer at a speed of 350-500 rpm to form a premix;

[0029] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0030] Preferably, the control conditions of the twin-screw extruder are:

[0031] Temperature setting: Zone 1 80±10℃, Zone 2 190±10℃, Zone 3 215±10℃, Zone 4 225±10℃, Zone 5 225±10℃, Zone 6 220±10℃, Zone 7 220±10℃, Zone 8 220±10℃, Zone 9 220±10℃, Die head 230±10℃;

[0032] Main machine speed: 32±3hz; Main machine current: 125±20A; Feeding speed: 40±3hz; Vacuum: -0.07±0.03MPa.

[0033] An integrated semi-transparent spray-free washing machine panel is made of an integrated semi-transparent spray-free washing machine panel material. The integrated semi-transparent spray-free washing machine panel is integrally injection-molded through a mold, and the thin part of the mold has a semi-transparent effect, with a thickness of 1-1.25mm, showing a light-transmitting effect, and the thickness of other places is 2.5mm-3mm, showing an opaque effect.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention can effectively improve the chemical resistance and toughness of the thermoplastic resin composition, reduce the possibility of cracking of the product, and improve the qualified rate of the product by adding high chemical resistance resins SAN and PMMA, core-shell toughening agent, maleic anhydride grafted compatibilizer, etc., wherein the toughening agent of the core-shell structure has good high impact resistance and transparency, and its shell is grafted with GMA with epoxy groups, which has high reaction activity, and GMA is a chain extender, which can react the terminal groups of the molecular chain to form a "bridge" to connect the molecular chains, so that the composite material has a higher modulus; the maleic anhydride grafted compatibilizer can significantly improve the tensile strength and impact strength of the composite material.

[0036] 2. The present invention can enhance the hardness of the washing machine panel by adding high-purity aluminum powder, making it more durable and not easily scratched or worn; at the same time, the addition of aluminum powder may have a certain effect on the fluidity of the resin, which helps to improve the formability of the washing machine panel, making it easier to process into the required shape and size, and at the same time improve the light transmittance of the washing machine panel. High-purity aluminum powder has good heat reflection properties, which can improve the heat resistance of the washing machine panel to a certain extent, so that it can maintain stable performance even in high temperature environments. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.

[0039] SAN resin: Zhenjiang Chimei, brand PN-118L

[0040] PMMA resin: Chimei, Taiwan, China, brand CM211

[0041] MABS resin: LG Chemical, brand TR-557

[0042] Maleic anhydride grafted compatibilizer: Jiayirong polymer, brand SAM-010

[0043] Aluminum powder: Zibo Ruixi Energy Co., Ltd.;

[0044] Antioxidant: BASF, 1076, 168

[0045] Lubricant: Indonesia EBS (ethylene bis stearamide)

[0046] The remaining unspecified raw materials were purchased from Aladdin and Alibaba.

[0047] Preparation of core-shell toughening agent

[0048] 150 mL of deionized water, 3.4 g of potassium disproportionated rosin acid, 2 g of potassium soap, 6 g of glucose, 4 g of ferrous sulfate, 0.4 g of sodium pyrophosphate and 100 g of polybutadiene latex were placed in a reactor, and nitrogen was introduced. The mixture was stirred at 65° C. for 15 min. After uniform mixing, a mixture of 42 g of styrene monomer, 30 g of methyl methacrylate monomer, 14 g of glycidyl methacrylate and 0.15 g of cumene hydroperoxide was slowly added into the reactor. After the addition was completed, the temperature was raised to 70° C., and the mixture was aged for 100 min. 5 mL of magnesium sulfate solution was added for demulsification and coagulation. The mixture was washed and dried to obtain a toughening agent with a core-shell structure.

[0049] The core-shell ratio of the prepared core-shell toughening agent is 75:25; the content of GMA is 7%.

[0050] Preparation Example 1

[0051] The preparation method of the thermoplastic resin composition comprises the following steps:

[0052] 300 g SAN, 300 g PMMA, 150 g core-shell toughening agent, and 50 g maleic anhydride grafted compatibilizer were blended in a high-speed mixer for 5 minutes to obtain a thermoplastic resin composition.

[0053] Preparation Example 2

[0054] The preparation method of the thermoplastic resin composition comprises the following steps:

[0055] 500 g of SAN, 500 g of PMMA, 200 g of a core-shell toughening agent, and 50 g of a maleic anhydride grafted compatibilizer were blended in a high-speed mixer for 10 minutes to obtain a thermoplastic resin composition.

[0056] Preparation Example 3

[0057] The preparation method of the thermoplastic resin composition comprises the following steps:

[0058] 500 g of SAN, 500 g of PMMA, 200 g of a core-shell toughening agent, and 100 g of a maleic anhydride grafted compatibilizer were blended in a high-speed mixer for 20 minutes to obtain a thermoplastic resin composition.

[0059] Preparation Example 4

[0060] The preparation method of the high-purity aluminum powder comprises the following steps:

[0061] 100g of aluminum powder was ball milled for 5h, and the aluminum powder was surface treated with silane coupling agent. 100g of aluminum powder after ball milling was placed in 150mL of anhydrous ethanol, stirred for 30min, filtered and dried. The washed aluminum powder was placed in 150mL of anhydrous ethanol solvent, ultrasonically dispersed for 30min, and after the ultrasonic treatment, 5g of silane coupling agent and 10g of deionized water were added, and the mixture was treated at a constant temperature of 50℃ for 6h. After filtering, vacuum drying was performed to obtain surface-modified high-purity aluminum powder.

[0062] Preparation Example 5

[0063] The preparation method of the high-purity aluminum powder comprises the following steps:

[0064] 100g of aluminum powder was ball-milled for 6h, and the surface of the aluminum powder after ball milling was treated with silane coupling agent. 100g of aluminum powder after ball milling was placed in 150mL of anhydrous ethanol, stirred for 30min, filtered and dried. The washed aluminum powder was placed in 150mL of anhydrous ethanol solvent, ultrasonically dispersed for 60min, and after the ultrasonication, 10g of silane coupling agent and 15g of deionized water were added, and the mixture was treated at a constant temperature of 50℃ for 4h. After filtration, vacuum drying was performed to obtain surface-modified high-purity aluminum powder.

[0065] Preparation Example 6

[0066] The preparation method of the high-purity aluminum powder comprises the following steps:

[0067] 100g of aluminum powder was ball milled for 8h, and the surface of the aluminum powder after ball milling was treated with silane coupling agent. 100g of aluminum powder after ball milling was placed in 150mL of anhydrous ethanol, stirred for 60min, filtered and dried. The washed aluminum powder was placed in 150mL of anhydrous ethanol solvent, ultrasonically dispersed for 60min, and after the ultrasonication, 5g of silane coupling agent and 10g of deionized water were added, and the mixture was treated at a constant temperature of 50℃ for 6h. After filtration, vacuum drying was performed to obtain surface-modified high-purity aluminum powder.

[0068] Example 1

[0069] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0070] S1: 950 g of the thermoplastic resin composition prepared in Preparation Example 1, 1 g of the high-purity aluminum powder prepared in Preparation Example 4, 2 g of antioxidant 1076, 5 g of weathering agent and 5 g of Indonesian EBS were mixed uniformly in a high-speed mixer at a speed of 350 rpm to form a premix;

[0071] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0072] The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of 1:2.3:1.

[0073] The control conditions of the twin-screw extruder are:

[0074] Temperature setting: Zone 1 70℃, Zone 2 180℃, Zone 3 215℃, Zone 4 225℃, Zone 5 225℃, Zone 6 220℃, Zone 7 220℃, Zone 8 220℃, Zone 9 220℃, Die head 230℃;

[0075] Main machine speed: 29hz; Main machine current: 105A; Feeding speed: 37hz; Vacuum: -0.08MPa.

[0076] Example 2

[0077] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0078] S1: 965 g of the thermoplastic resin composition prepared in Preparation Example 2, 5 g of the high-purity aluminum powder prepared in Preparation Example 5, 6 g of antioxidant 1010, 8 g of weathering agent and 7 g of Indonesian EBS were mixed uniformly in a high-speed mixer at a speed of 400 rpm to form a premix;

[0079] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0080] The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of 1:2.3:1.

[0081] The control conditions of the twin-screw extruder are:

[0082] Temperature setting: Zone 1 70℃, Zone 2 180℃, Zone 3 215℃, Zone 4 225℃, Zone 5 225℃, Zone 6 220℃, Zone 7 220℃, Zone 8 220℃, Zone 9 220℃, Die head 230℃;

[0083] Main machine speed: 29hz; Main machine current: 105A; Feeding speed: 37hz; Vacuum: -0.08MPa.

[0084] Example 3

[0085] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0086] S1: 980 g of the thermoplastic resin composition prepared in Preparation Example 3, 10 g of the high-purity aluminum powder prepared in Preparation Example 6, 10 g of antioxidant 168, 10 g of weathering agent and 10 g of Indonesian EBS were mixed uniformly in a high-speed mixer at a speed of 500 rpm to form a premix;

[0087] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0088] The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of 1:2.3:1.

[0089] The control conditions of the twin-screw extruder are:

[0090] Temperature setting: Zone 1 70℃, Zone 2 180℃, Zone 3 215℃, Zone 4 225℃, Zone 5 225℃, Zone 6 220℃, Zone 7 220℃, Zone 8 220℃, Zone 9 220℃, Die head 230℃;

[0091] Main machine speed: 29hz; Main machine current: 105A; Feeding speed: 37hz; Vacuum: -0.08MPa.

[0092] Example 4

[0093] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0094] S1: 950 g of the thermoplastic resin composition prepared in Preparation Example 1, 1 g of the high-purity aluminum powder prepared in Preparation Example 4, 2 g of antioxidant 1076, 5 g of weathering agent and 5 g of Indonesian EBS were mixed uniformly in a high-speed mixer at a speed of 350 rpm to form a premix;

[0095] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0096] The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of 1.5:3:1.

[0097] The control conditions of the twin-screw extruder are:

[0098] Temperature setting: Zone 1 90℃, Zone 2 200℃, Zone 3 225℃, Zone 4 235℃, Zone 5 235℃, Zone 6 230℃, Zone 7 230℃, Zone 8 230℃, Zone 9 230℃, Die head 240℃;

[0099] Main machine speed: 35hz; Main machine current: 145A; Feeding speed: 43hz; Vacuum: -0.05MPa.

[0100] Example 5

[0101] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0102] S1: 965 g of the thermoplastic resin composition prepared in Preparation Example 2, 5 g of the high-purity aluminum powder prepared in Preparation Example 5, 6 g of antioxidant 1010, 8 g of weathering agent and 7 g of Indonesian EBS were mixed uniformly in a high-speed mixer at a speed of 400 rpm to form a premix;

[0103] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0104] The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of 1.5:3:1.

[0105] The control conditions of the twin-screw extruder are:

[0106] Temperature setting: Zone 1 90℃, Zone 2 200℃, Zone 3 225℃, Zone 4 235℃, Zone 5 235℃, Zone 6 230℃, Zone 7 230℃, Zone 8 230℃, Zone 9 230℃, Die head 240℃;

[0107] Main machine speed: 32hz; Main machine current: 125A; Feeding speed: 40hz; Vacuum: -0.07MPa.

[0108] Example 6

[0109] A method for preparing an integrated semi-transparent spray-free washing machine panel material comprises the following steps:

[0110] S1: 980 g of the thermoplastic resin composition prepared in Preparation Example 3, 10 g of the high-purity aluminum powder prepared in Preparation Example 6, 10 g of antioxidant 168, 10 g of weathering agent and 10 g of Indonesian EBS were mixed uniformly in a high-speed mixer at a speed of 500 rpm to form a premix;

[0111] S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

[0112] The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol, and polyethylene glycol monomethyl ether methacrylate in a mass ratio of 1.5:3:1.

[0113] The control conditions of the twin-screw extruder are:

[0114] Temperature setting: Zone 1 90℃, Zone 2 200℃, Zone 3 225℃, Zone 4 235℃, Zone 5 235℃, Zone 6 230℃, Zone 7 230℃, Zone 8 230℃, Zone 9 230℃, Die head 240℃;

[0115] Main machine speed: 35hz; Main machine current: 145A; Feeding speed: 43hz; Vacuum: -0.06MPa.

[0116] Comparative Example 1

[0117] The difference between this comparative example and Example 1 is that the thermoplastic resin composition prepared in Preparation Example 1 is replaced by a common commercially available MABS resin, the manufacturer of which is LG Chemical, with a brand name of TR-557.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 1 is that the high-purity aluminum powder prepared in Preparation Example 4 is replaced by ordinary commercially available crude aluminum powder purchased from Zibo Ruixi Energy Co., Ltd.

[0120] Comparative Example 3

[0121] The difference between this comparative example and Example 1 is that no weathering agent is added.

[0122] Comparative Example 4

[0123] The difference between this comparative example and Example 1 is that the weathering agent is replaced by the ultraviolet absorber UV531.

[0124] The washing machine panel materials prepared in the above Examples 1-6 and Comparative Examples 1-4 were injection molded and subjected to performance tests. The results are shown in Tables 1 and 2:

[0125] Test standard:

[0126] Tensile strength, elongation at break: GB / T1040.1, test conditions: 50mm / min;

[0127] Flexural strength, flexural modulus: GB / T 9341, test conditions: 2mm / min;

[0128] Impact strength: GBT1843, test conditions: 5.5J;

[0129] Melt index: GB / T 3682, test conditions: 220℃ / 10kg;

[0130] Light transmittance: GB / T2410, test conditions: 23℃.

[0131] Gloss: GB / T 8807, measuring angle: 60°.

[0132] Table 1

[0133]

[0134] Table 2

[0135]

[0136]

[0137] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An integrated semi-transparent spray-free washing machine panel material, characterized in that: The invention is made of the following raw materials in parts by weight: 95-98 parts of a thermoplastic resin composition, 0.1-1 parts of high-purity aluminum powder, 0.2-1.0 parts of an antioxidant, 0.5-1.0 parts of a weathering agent, and 0.5-1.0 parts of a lubricant.

2. The one-piece semi-transparent spray-free washing machine panel material according to claim 1, characterized in that: The preparation method of the thermoplastic resin composition comprises the following steps: Styrene acrylonitrile copolymer, polymethyl methacrylate, core-shell toughening agent and maleic anhydride grafted compatibilizer are blended in a high-speed mixer for 5-20 minutes to obtain a thermoplastic resin composition.

3. The one-piece semi-transparent spray-free washing machine panel material according to claim 2, characterized in that: The mass ratio of the styrene acrylonitrile copolymer, polymethyl methacrylate, core-shell toughening agent and maleic anhydride grafted compatibilizer is (30-50): (30-50): (10-25): (2-10); The maleic anhydride grafted compatibilizer has a maleic anhydride content of 10%; The core-shell toughening agent has a core-shell ratio of (60:40)-(80:20); and the content of GMA is 0-8%.

4. The one-piece semi-transparent spray-free washing machine panel material according to claim 3, characterized in that: The method for preparing the core-shell toughening agent comprises the following steps: Deionized water, emulsifier, reducing agent, chelating agent and polybutadiene latex are placed in a reaction kettle, and nitrogen is introduced. The mixture is stirred at 65°C for 15-30 minutes. After uniform mixing, a mixture of styrene monomer, methyl methacrylate monomer, glycidyl methacrylate and initiator is slowly added into the reaction kettle. After the addition is completed, the temperature is raised to 70°C, and the mixture is aged for 60-120 minutes. A magnesium sulfate solution is added for demulsification and coagulation, and the mixture is washed and dried to obtain a toughening agent with a core-shell structure.

5. The one-piece semi-transparent spray-free washing machine panel material according to claim 4, characterized in that: The emulsifier is one or more of potassium disproportionate rosin acid, potassium soap of fatty acid, and sodium dodecylbenzene sulfonate; The reducing agent is one or more of glucose, ferrous sulfate, and sodium formaldehyde sulfoxylate; The chelating agent is one or more of sodium pyrophosphate, tetrasodium ethylenediaminetetraacetic acid, and sodium tripolyphosphate; The initiator is one or more of dicumyl peroxide, cumyl hydroperoxide and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane.

6. The one-piece semi-transparent spray-free washing machine panel material according to claim 1, characterized in that: The preparation method of the high-purity aluminum powder comprises the following steps: The aluminum powder crude product is ball-milled for 5-8 hours, and the surface of the aluminum powder after ball milling is treated with a silane coupling agent. The aluminum powder after ball milling is placed in anhydrous ethanol, stirred for 30-60 minutes, filtered, and dried. The washed aluminum powder is placed in anhydrous ethanol solvent and ultrasonically dispersed for 30-60 minutes. After the ultrasonication, a certain amount of silane coupling agent and a corresponding proportion of deionized water are added, and the mixture is treated at a constant temperature of 50° C. for 4-6 hours. After filtering, vacuum drying is performed to obtain surface-modified high-purity aluminum powder; The silane coupling agent is one or more of KH540, KH550 and KH570, and the mass ratio of the washed aluminum powder, anhydrous ethanol, silane coupling agent and deionized water is 100:(150-200):(5-10):(10-20).

7. The one-piece semi-transparent spray-free washing machine panel material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1076, antioxidant 1010 or antioxidant 168; The lubricant is one or more of polyethylene wax, ethylene bis stearic acid amide and calcium stearate.

8. The one-piece semi-transparent spray-free washing machine panel material according to claim 1, characterized in that: The weathering agent is prepared by compounding 2-(2'-hydroxy 5'-tert-octylphenyl)benzotriazole, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol and polyethylene glycol monomethyl ether methacrylate in a mass ratio of (1-1.5):(2.3-3):

1.

9. A method for preparing the integrated semi-transparent spray-free washing machine panel material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Mixing the thermoplastic resin composition, high-purity aluminum powder, antioxidant, weathering agent and lubricant in a high-speed mixer at a speed of 350-500 rpm to form a premix; S2: The premix formed in S1 is added from the main feeding port and granulated in a twin-screw extruder to obtain a washing machine panel material.

10. The method for producing an integrated semi-transparent spray-free washing machine panel material according to claim 9, characterized in that: The control conditions of the twin-screw extruder are: Temperature setting: Zone 1 80±10℃, Zone 2 190±10℃, Zone 3 215±10℃, Zone 4 225±10℃, Zone 5 225±10℃, Zone 6 220±10℃, Zone 7 220±10℃, Zone 8 220±10℃, Zone 9 220±10℃, Die head 230±10℃; Main machine speed: 32±3hz; Main machine current: 125±20A; Feeding speed: 40±3hz; Vacuum: -0.07±0.03MPa.

11. An integrated semi-transparent spray-free washing machine panel made of the integrated semi-transparent spray-free washing machine panel material according to any one of claims 1 to 8, characterized in that: The one-piece semi-transparent spray-free washing machine panel is integrally injection-molded through a mold, and the thin part of the mold has a semi-transparent effect, with a thickness of 1-1.25mm, showing a light-transmitting effect, and the thickness of other places is 2.5mm-3mm, showing an opaque effect.